Synthesis, biological activities, and docking studies of d-pantolactone derivatives as novel FAS inhibitors. Issue 20 (15th October 2019) - Fang, Hua; He, Jianlin; Ran, Tan; Chen, Hui; Jin, Wenhui; Tang, Bowen; Hong, Zhuan; Fang, Meijuan
Graphical abstract: Thed -pantolactone derivative, ( R )-4-methoxy-benzoic acid 4, 4-dimethyl-2-oxo-tetrahydro-furan-3-yl ester (3m ), exhibited fatty acid synthase inhibitory activity with IC50 value of 13.68 ± 2.79 μM. Like reference compoundC75, compound3m also showed similar inhibition of lipid accumulation on the proliferation of HepG2 cells. Molecular docking was further used to predict the interaction model of3m and KR domain of human fatty acid synthase. Abstract: A novel series of fatty acid synthase (FAS) inhibitors with D-(−)-pantolactone moiety and potential utility for the treatment of obesity were designed, synthesized and characterized, in which the structure of compound3k was further confirmed by single X-ray diffraction. The mouse FAS inhibitory activity of synthesized compounds was evaluated. Major synthesized compounds (except3g, 3i, 3k, 3l, and3n ) exhibited moderate FAS inhibitory properties with IC50 values in the range of 13.68 ± 1.52–33.19 ± 1.39 μM, reference inhibitorC75 has IC50 value of 13.86 ± 2.79 μM. Eight compounds (3c, 3d, 3e, 3f, 3j, 3m, 3q and3r ) also displayed inhibitory effect on lipid accumulation in human HepG2 cells. Additionally, the molecular docking study revealed that compound3m having good inhibition activity against FAS and lipid accumulation also showed promising binding affinities with hFAS, while its binding model with hFAS (PDB ID: 4PIV) was different from that of reference compoundC75 .